2013
DOI: 10.4103/2230-8210.113724
|View full text |Cite
|
Sign up to set email alerts
|

Impact of alcohol use on thyroid function

Abstract: Alcohol is one of the commonest illicit psychoactive substances consumed globally and is the world's third largest risk factor for disease and disability. It has been reported to have multiple effects on the hypothalamo-pituitary-thyroid axis and the functioning of the thyroid gland. It has been reported to cause direct suppression of thyroid function by cellular toxicity, and indirect suppression by blunting thyrotropin-releasing hormone response. It causes a decrease of peripheral thyroid hormones during chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 61 publications
(80 reference statements)
6
28
0
2
Order By: Relevance
“…Interestingly, in our cohort, fT4 levels could be associated with alcohol and Her2 positivity. Alcohol has been reported to cause direct suppression of thyroid function, which is in line with our findings [31]. However, the correlation of Her2 positivity and fT4 has not been described yet.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, in our cohort, fT4 levels could be associated with alcohol and Her2 positivity. Alcohol has been reported to cause direct suppression of thyroid function, which is in line with our findings [31]. However, the correlation of Her2 positivity and fT4 has not been described yet.…”
Section: Discussionsupporting
confidence: 92%
“…Endocrinol in 1980 that also shows a markedly reduced T3 level in patients with alcoholic cirrhosis. 18 In this study T4 levels were found within normal range in 65 patients (85.5 percent) whereas 11 patients had a low serum T4 level. So, normal level of T4 was found in significant majority cases.…”
Section: Resultssupporting
confidence: 42%
“…In addition, maternal alcohol use, smoking and substance use during pregnancy were not universally included across the studies, which may have confounded the associations of interest. These factors have been found to increase the risk of thyroid hormone imbalance during pregnancy, consequently affecting the pregnancy outcome (58,59,60,61). Evidence also suggests that exposure to maternal tobacco, cannabis and alcohol use during pregnancy may lead to detrimental neurologic effects on the offspring (62).…”
Section: Discussionmentioning
confidence: 99%